The role of the Sharazurs in administrative and scientific aspects - Faida Ali Mohammed (QALAAI ZANIST JOURNAL, 2023)
The research is entitled (Role of Sharazurs in the administrative and scientific aspects) which discusses the role of Sharazoori in the rank and position outside their homeland or we can say the positions they had in the management of government institutions abroad this is due to the strength, ability and intelligence of the people of Sharazur, Because they were capable in terms of administration, such as ambassadors and judges in Syria, in addition to the post of minister in Morocco, as well as the post of governor,The people of Sharazoor had an important position not only in terms of administration but also in terms of science, Talented personalities such as Shams al-Din al-Shahrzuri, who played an important role in the management of the school of al-Qaymri, also received the post of judge, which shows the ability and intelligence of this personality. In addition to the science of the Qur'an, Tafsir, Hadith and jurisprudence, they played an important role, They also played a role in philosophy and logic, so they played a role in Islamic civilization like any other tribe. We can say that they have their fingerprints because they are the only tribe that has been recognized as a tribe abroad, Give them important positions in the country's administration and trust them. The people of Sharazur have been able to record an important position in Islamic civilization in which the great scholars of Sharazur had participated in the development of Islamic civilization in all kinds of religion, politics, administration and science between the fifth and eighth centuries AH.